Topological analysis of carbon flux during multi-stress adaptation in Halomonas sp AAD12 - SAYAR, NİHAT ALPAGU (UNIV CATOLICA DE VALPARAISO, 2015)
Background: Osmolytes with their effective stabilizing properties are accumulated as protectants not only against salinity but also against denaturing harsh environmental stresses such as freezing, drying, high temperatures, oxygen radicals and radiation. The present work seeks to understand how Halomonas sp. AAD12 cells redirect carbon flux specifically to replenish reactions for biomass and osmolyte synthesis under changing salinity and temperature. To accomplish this goal, a combined FBA-PCA approach has been utilized. Results: Experimental data were collected to supply model constraints for FBA and for the verification of the model predictions, which were satisfactory. With restrictions on the various combinations of selected anaplerotic paths (reactions catalyzed by phosphoenolpyruvate carboxylase, pyruvate carboxylase or glyoxylate shunt), two major phenotypes were found. Moreover, under high salt concentrations, when the glucose uptake rate was over 1.1 mmoL DCW-1 h(-1), an overflow metabolism that led to the synthesis of ethanol caused a slight change in both phenotypes. Conclusions: The operation of the glyoxylate shunt as the major anaplerotic pathway and the degradation of 6-phosphogluconate through the Entner-Doudoroff Pathway were the major factors in causing a distinction between the observed phenotypes. (C) 2015 Pontificia Universidad Catolica de Valparaiso. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: Flux balance analysis; Flux distribution; Halomonas sp AAD12; Halophilic; Principle component analysis; COMPATIBLE SOLUTES; ECTOINE; SALT; CAPABILITIES